(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
There are numerous benefits to treating wastewater using bacteriological and phytochemical methods. Microorganisms are employed in bioremediation to break down or reduce the concentration of harmful substances in polluted environments. In phytoremediation, green plants absorb harmful pollutants and restore abiotic conditions. These methods are often more cost-effective and environmentally friendly compared to conventional approaches. The synergy between plants and microorganisms is effectively utilized in processes like constructed wetlands or wastewater treatment wetlands, which offer several advantages, including low energy requirements, aesthetic appeal, and habitat creation for various wildlife species. However, the combined application of microorganisms and plants in wastewater treatment has not been thoroughly investigated or fully understood. Therefore, this analysis aims to evaluate the roles of microorganisms and plants in wastewater treatment, their interactions, and the conditions that facilitate these processes.